Effects of digital and non-digital parental distraction on parent-child interaction and communication - Chamam, Souhir; Forcella, Alexia; Musio, Nadia; Quinodoz, Florence; Dimitrova, Nevena (Frontiers in Child and Adolescent Psychiatry, 2024)
Technoference, namely parental screen use in the presence of a child, is a widespread phenomenon that has negative effects on parent-child interaction and communication. When parents use screens around their children there are fewer interactions and parents are less contingent and responsive to the child. Additionally, children show more negative behaviors, such as whining, frustration, and outbursts. Communication is also affected—parents speak and gesture less towards their children and, in turn, children are less likely to develop their language abilities. It remains unclear, however, if parental distraction due to screen use affects parent-child interaction and communication more negatively compared to non-digital parental distraction. Fifty-two parent-child dyads (mean child age = 22 months, range 12-36 months) first played for 5 min (Time 1); then (Time 2), the parent was asked to fill out a questionnaire on a tablet (screen condition), on a printed form (paper-pen condition) or was not interrupted (control condition). Interactive quality was assessed at Time 1 and Time 2 using the Coding Interactive Behavior scale. Communication was assessed by coding the number of word tokens and types during Time 1 and Time 2; child gestures were also coded. Results revealed that when parents were distracted—either by the paper-pen or the screen questionnaire—the quality of the interaction significantly deteriorated (ps≤.01) and the quantity of parental communication significantly declined (ps≤.012). Importantly, the nature of the distraction did not matter: there were no significant differences between the paper-pen and the screen distraction conditions across Time 2 (ps≥.59). Findings suggest that parental distraction matters for the quality of interaction and the amount of communicative bids, independently on whether parents were distracted by a digital or non-digital activity. These findings likely relate to complex factors related to young children’s experiences and habits with parental screen use.